The Effect of Distance Learning (PJJ) and Motivation Towards Penjas Learning Outcomes In YPKPM Ambon Christian High School Students - Yulia Tomasoa; Emma Rumahlewang; J. Solissa (Peneliti.net, 2021)
This study aims to analyze: (1) multiple linear regression equations (2) the effect of distance learning (PJJ) on physical education learning outcomes, (3) ) the influence of motivation on learning outcomes of Physical Education, and (4) the effect of distance learning (PJJ) and motivation on learning outcomes of Physical Education. This experimental research uses a simple and regression designmultiple linear regression design. The subjects in this study were students of class XI MIA2 SMA Kristen YPKPM Ambon. The data analysis technique uses multiple linear regression analysis. Based on hypothesis testing, the results of this study are: (1) the multiple regression equation Y on X1and X2is Y = b₀ + b₁X₁ + b₂X, (2) there is an influence between distance learning (PJJ) on the learning outcomes of Physical Education. With the tcalculationhit of 2.23 (3) there is an effect of PJJ on learning outcomes of Physical Education, the calculation of thit is 2.4 (3) there is an effect of motivation on learning outcomes ofwith the calculation of flearning outcomes.hit Physical Education,4,714, (4) there is an effect of distance learning andmotivation towards learning outcomes of Physical Education with multiple correlation significant test. Conclusions: (1) the multiple regression equation obtained from this study Y = b₀ + b₁X₁ + b₂X₂ = 1.749 + 0.540 X1 + 0.449 X2. (2) the coefficient of determination is 29.10%, (3) the F-test hypothesis is together / stimulant can be explained that distance learning variables and motivation together have an effect on the learning outcomes of class XI MIA 2 SMA YPKPM Ambon. This is indicated by the results of the F-count 4.717.